Towards an unified computational model of natural language (Linguamática, 2013)
What formalism should be used in order to formalize natural language? That formalism must be able to describe all sequences of natural languages in a right way. Moreover, as long as possible, that formalism must be simple, with a reduced computational cost. This question has triggered a great controversy among the main branches of generative Linguistics: Transformational Grammar and Unification Grammars. The claim of this paper is that, despite discrepancies, these linguistic models formalize natural language by means of the same formal language. This is a well-defined formal language: the context-sensitive language of Noam Chomskyâ€™s hierarchy. So, from the point of view of this paper, nowadays, Linguistics can oâ†µer an unified computational model of natural language.